Nasal nitric oxide levels in primary ciliary dyskinesia, cystic fibrosis and healthy children - Elif Güney; Nagehan Emiralioğlu; Güzin Cinel; Ebru Yalçın; Deniz Doğru; Nural Kiper; Hayriye Uğur Özçelik (The Turkish Journal of Pediatrics)
Primary ciliary dyskinesia (PCD) is a rare, inherited disorder characterized by recurrent respiratory tract infections. The measurement of nasal nitric oxide (nNO) is an important test for the diagnosis of PCD. In this study, we aim to evaluate NIOX-MINOÒ, which is an easily applicable method for measuring nNO, in the diagnosis of patients with PCD and define diagnostic cut-off levels. Furthermore, determining the normal limits of nNO in healthy children and investigating nNO levels of children with cystic fibrosis (CF) are the other aims of this study. The children included in this study were 5 to 18.5 years old, 46 of them had PCD, 44 had CF and 200 were healthy children. To our knowledge, this work contains the widest population compared to previous studies. Subjects receiving steroids or antibiotics or those with any acute respiratory tract infection, asthma or allergic rhinitis were not included in the study. Mean nNO levels were found as 10.4, 22.8 and 21.0 ppb in PCD, CF and healthy children, respectively. The nNO levels for PCD patients were found significantly lower than children with CF and the control groups (p < 0.05). In this study, the diagnostic nNO cut-off level between PCD and the other two groups was determined to be < 11.5 ppb with %83.6 specificity and %67.4 sensitivity. The screening of nNO with NIOX-MINO method provides early diagnose before mucosal biopsy of patients who are suspected to have PCD and therefore, prevents co-morbidities and prolongs survival with early treatment.